2021
DOI: 10.1016/j.memsci.2020.118943
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical ZIF-8 composite membranes: Enhancing gas separation performance by exploiting molecular dynamics in hierarchical hybrid materials

Abstract: Hierarchical ZIF-8 Mixed matrix membranes Gas separation PolyimideMixed matrix membranes (MMM) incorporating metal-organic framework (MOF) fillers have gained increasing attention in addressing environmental and sustainability challenges. Hierarchical materials combining pore sizes of different length scales are expected to facilitate molecular diffusion and mass transfer for the optimization of catalysis and separation processes. Herein, a novel preparation method for hierarchical ZIF-8 (H-ZIF-8) particles is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 69 publications
(79 reference statements)
1
10
0
Order By: Relevance
“…This might have been related to the lower solubility of gas molecules with increasing temperature. The adverse impact of temperature on sorption enthalpy would have affected the transport and sorption behavior of gases over the membrane [ 26 ]. From the obtained results, a maximum CO 2 permeability of 609.1 Barrer was achieved at a feed pressure of 3.5 bar and a temperature of 40 °C.…”
Section: Resultsmentioning
confidence: 99%
“…This might have been related to the lower solubility of gas molecules with increasing temperature. The adverse impact of temperature on sorption enthalpy would have affected the transport and sorption behavior of gases over the membrane [ 26 ]. From the obtained results, a maximum CO 2 permeability of 609.1 Barrer was achieved at a feed pressure of 3.5 bar and a temperature of 40 °C.…”
Section: Resultsmentioning
confidence: 99%
“…The highest coefficient of Henry's law (K D ) observed on M0 primarily due to the overall sorption governed by Henry' solubility law sorption. [40] It can be seen that all dual-mode parameters (K D , C 0 H , and b) decreased after the inclusion of MIL-125 (Ti) and NH 2 -MIL-125 (Ti) fillers into the polymer matrix. The reduction of the coefficient of Henry's law (K D ) shows that the addition of MIL-125 (Ti) and NH 2 -MIL-125 (Ti) fillers has reduced the interaction between the CH 4 gas molecule and the membrane due to nonpolar character of CH 4 , and therefore, less CH 4 gas molecule were dissolved in the membrane.…”
Section: Co 2 Plasticization Behaviormentioning
confidence: 92%
“…The CO 2 sorption of M1, and M2 showed significantly higher than that of M0 owing to the high adsorption of filler caused by the increased filler's surface area. [40] Referring to Figure 3, it can be observed that the sorption isotherms obtained from M0, M1, and M2 are concave to the vertical axis at low pressure and tends to approach straight line at higher pressure. This results show that CO 2 sorption is dominated by Langmuir mode (C H ) when the pressure is low, F I G U R E 2 CO 2 plasticization pressure of membranes meanwhile the CO 2 sorption is followed Henry mode (C D ) at high pressure.…”
Section: Co 2 Plasticization Behaviormentioning
confidence: 92%
See 2 more Smart Citations